Real-Time Positron Emission Tomography Evaluation of Topotecan Brain Kinetics after Ultrasound-Mediated Blood-Brain Barrier Permeability - Andrei Molotkov; Patrick Carberry; Martin A. Dolan; Simon Joseph; Sidney Idumonyi; Shunichi Oya; John Castrillon; Elisa E. Konofagou; Mikhail Doubrovin; Glenn J. Lesser; Francesca Zanderigo; Akiva Mintz (MDPI AG, 2021)
Glioblastoma (GBM) is the most common primary adult brain malignancy with an extremely poor prognosis and a median survival of fewer than two years. A key reason for this high mortality is that the blood-brain barrier (BBB) significantly restricts systemically delivered therapeutics to brain tumors. High-intensity focused ultrasound (HIFU) with microbubbles is a methodology being used in clinical trials to noninvasively permeabilize the BBB for systemic therapeutic delivery to GBM. Topotecan is a topoisomerase inhibitor used as a chemotherapeutic agent to treat ovarian and small cell lung cancer. Studies have suggested that topotecan can cross the BBB and can be used to treat brain metastases. However, pharmacokinetic data demonstrated that topotecan peak concentration in the brain extracellular fluid after systemic injection was ten times lower than in the blood, suggesting less than optimal BBB penetration by topotecan. We hypothesize that HIFU with microbubbles treatment can open the BBB and significantly increase topotecan concentration in the brain. We radiolabeled topotecan with 11C and acquired static and dynamic positron emission tomography (PET) scans to quantify [11C] topotecan uptake in the brains of normal mice and mice after HIFU treatment. We found that HIFU treatments significantly increased [11C] topotecan brain uptake. Moreover, kinetic analysis of the [11C] topotecan dynamic PET data demonstrated a substantial increase in [11C] topotecan volume of distribution in the brain. Furthermore, we found a decrease in [11C] topotecan brain clearance, confirming the potential of HIFU to aid in the delivery of topotecan through the BBB. This opens the potential clinical application of [11C] topotecan as a tool to predict topotecan loco-regional brain concentration in patients with GBMs undergoing experimental HIFU treatments.